Multifactorial Risk Factors of Hypertension in Patients Aged 45-55 Years in Kota Kotamobagu: A Cross-Sectional Study - Ake Royke Calvin Langingi; Grace Irene Viodyta Watung; Sudirman Sudirman; Mareyke Yolanda Lusia Sepang; Siska Sibua; Ignatia Yohana Rembet (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Hypertension in adults aged 45-55 years has a significant impact on heart health and morbidity. Hypertension is estimated to affect 1.56 billion people by 2025 and become a leading cause of death. In Indonesia, the prevalence is 18.7% in the 45-54 age group, with North Sulawesi ranking third highest. In Kotamobagu, hypertension ranks second among non-communicable diseases with 24,956 cases. This high number emphasizes the importance of prevention and control. A deep understanding of modifiable risk factors is needed to develop effective prevention strategies. This study aims to identify the primary risk factors that influence the prevalence of hypertension in the adult population of Kotamobagu City. This descriptive-quantitative study used an analytical observational study design with a cross-sectional technique. The study was conducted in Kotamobagu City, North Sulawesi Province, Indonesia, from July to August 2024. This study used an analytical observational design with a cross-sectional method, data collection using a digital sphygmomanometer to measure blood pressure, an Easy Touch GCU Meter to analyze dyslipidemia and blood sugar levels, and a questionnaire to assess physical activity, diet, salt consumption, alcohol consumption, and smoking habits. The sample consisted of 388 hypertensive patients selected using the Slovin Formula, and the statistical analysis used was chi-square. The results showed that diet, dyslipidemia, obesity, high salt consumption, alcohol, and smoking were significantly correlated with hypertension. Based on the odds ratio, the factors that had the strongest relationship with the incidence of hypertension were poor diet (OR = 1.53), dyslipidemia (OR = 1.49), and excessive salt consumption (OR = 1.46).